Population dynamics of the southern short-tailed opossum (Monodelphis dimidiata) in the Pampas of Argentina - Baladron Felix, Alejandro Victor (2012)
The genus Monodelphis is one of the most species rich among Neotropical marsupials. Despite this, little is known about most of the species. One of the most enigmatic species is M. dimidiata, a small terrestrial opossum that inhabits the Pampean region of Argentina, which is suspected to be a semelparous breeder. From 2005 to 2008, we conducted seasonal live trapping in near-pristine marshy grasslands and agroecosystems of the Pampean region in order to evaluate the population trends of this species and the occurrence of semelparity. M. dimidiata was characterised by a low abundance in the study area. The average density was higher in grasslands than in agroecosystems, and it appeared to be influenced by vegetative cover. The onset of the breeding season occurred during spring when the opossums showed a sudden increase in body size. Given that mature individuals were not found beyond autumn, the findings suggest an annual cycle for this species. In addition, this abrupt maturation resulted in a pronounced sexual dimorphism that, together with the strong reproductive seasonality and a likely polygynous mating system, supported previous claims that the species is semelparous. Our results also emphasise the importance of native grassland habitat for the maintenance of stable populations of M. dimidiata.